Between dualism and integration - Durnik, Mitja (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2012)
Two different approaches to development in disadvantaged communities are represented. The first one, community economic development, which is widely applied in Canada, is a community-based approach with a relevant role of the state in supporting development activities within a disadvantaged community. The second one, the National Program of Measures concerning Roma Communities within the Period 2010-2015, was established by the Slovenian government and represents a complex, broad government strategy which tries to respond to acute problems of underdevelopment in areas inhabited by Roma peoples. However, there is no single answer about the level and mode of state involvement in development policies. The fact is, however, that power relations to a great extent create the possibility for more or less radical social action.
Keywords: Slovenia; Slovenija; Canada; Kanada; Romi; marginalizirane skupine; staroselci